2018
DOI: 10.1371/journal.pone.0200260
|View full text |Cite
|
Sign up to set email alerts
|

The myodural bridges' existence in the sperm whale

Abstract: Recent studies have identified that the myodural bridge (MDB) is located between the suboccipital muscles and cervical dura mater in the posterior atlanto-occipital interspace within humans. The myodural bridge has been considered to have a significant role in physiological functions. However, there is little information about the myodural bridge in marine mammals; we conducted this study to investigate and examine the morphology of the myodural bridge in a sperm whale. We also aim to discuss the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
4
18
1
Order By: Relevance
“…This direct connection between the RCDmi and the SDM of the Nephocaena phocaenoides might create a more pronounced effect of the RCDmi muscle on the SDM [19]. Furthermore, the present authors have confirmed that sperm whales have two different origins of their MDB: one origin is from the ODB (occipital dural bridge) which originates from the periosteal surface of the occiput and fuses with the dura mater [20], and the other bridge (MDB) originates from the RCDmi, which transmits the tension from the RCDmi to the dura mater. The MDB stabilizes the dura mater, the spinal cord, and the ODB [20].…”
supporting
confidence: 75%
See 4 more Smart Citations
“…This direct connection between the RCDmi and the SDM of the Nephocaena phocaenoides might create a more pronounced effect of the RCDmi muscle on the SDM [19]. Furthermore, the present authors have confirmed that sperm whales have two different origins of their MDB: one origin is from the ODB (occipital dural bridge) which originates from the periosteal surface of the occiput and fuses with the dura mater [20], and the other bridge (MDB) originates from the RCDmi, which transmits the tension from the RCDmi to the dura mater. The MDB stabilizes the dura mater, the spinal cord, and the ODB [20].…”
supporting
confidence: 75%
“…Furthermore, the present authors have confirmed that sperm whales have two different origins of their MDB: one origin is from the ODB (occipital dural bridge) which originates from the periosteal surface of the occiput and fuses with the dura mater [20], and the other bridge (MDB) originates from the RCDmi, which transmits the tension from the RCDmi to the dura mater. The MDB stabilizes the dura mater, the spinal cord, and the ODB [20]. The MDB, observed in the atlanto-occipital interspace of penguins, is primarily composed of dense connective tissue fibers originating from the RCDmi muscle.…”
supporting
confidence: 75%
See 3 more Smart Citations